Engineered Cell Membrane Vesicles Expressing CD40 Alleviate System Lupus Nephritis by Intervening B Cell Activation. Issue 3 (5th January 2023) - Fang, Tianliang; Li, Baoqi; Li, Meng; Zhang, Yuli; Jing, Zhangyan; Li, Yuan; Xue, Tianyuan; Zhang, Zhirang; Fang, Wenli; Lin, Zhongda; Meng, Fanqiang; Li, Liyan; et al.
Abstract: Immune intervention of B cell activation to blockade the production of autoantibodies provokes intense interest in the field of systemic lupus erythematosus (SLE) therapy development. Although the survival rate for SLE is improved, many patients die untimely. Engineered cell membrane vesicles manifest remarkable capacity of targeted drug delivery and immunomodulation of immune cells such as B cells. Herein, this work engineered cellular nanovesicles (NVs) presenting CD40 (CD40 NVs) that can blunt B cells and thus alleviate SLE. CD40 NVs disrupt the CD40/CD40 ligand (CD40L) costimulatory signal axis through the blockade of CD40L on CD4 + T cells. Therefore, the CD40 NVs restrain the generation of the germinal center structure and production of antibodies from B cells. Furthermore, immunosuppressive drug mycophenolate mofetil (MMF) is also encapsulated in the vesicles (MMF‐CD40 NVs), which is employed to deplete immunocytes including B cells, T cells, and dendritic cells. Together, CD40 NVs are promising formulations for relieving autoimmunity and lupus nephritis in MRL/lpr mice. Abstract : Genetically engineered cell membrane vesicles displaying CD40 can blunt B cells through disrupting the CD4 + T/B cell interaction. Thus, CD40 nanovesicles can restrain the generation of the germinal center structure and production of antibody from B cells. Moreover, immuno‐suppressive drug encapsulated in the vesicles can achieve combined therapy. Overall, an engineered biomimetic vesicle is developed to alleviate lupus nephritis by bluntinvvg B cells.